2020
DOI: 10.1101/2020.07.31.20165811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 case-fatality rate and demographic and socioeconomic influencers: a worldwide spatial regression analysis based on country-level data

Abstract: We used the COVID-19 dataset obtained from the Our World in Data website and investigated the associations between COVID-19 CFR and nine country-level indices of 209 countries/territories using the Matern correlation regression model. Spatial dependence among the data was controlled using the latitude and longitude of the centroid of the countries/territories. Stratified analyses were conducted by economic level and COVID-19 testing policy. The average of country/territory-specific COVID-19 CFR is about 2-3% w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…As of April 10, 2020; 1,521,252 people were diagnosed with a COVID-19 infection, and 92,798 died from the virus (WHO, 2020). With a case fatality rate estimated around 2-3% (Cao et al, 2020), COVID-19 represents a potent and salient global threat. So far, the health and economic impacts of COVID-19 have been subjected to extensive assessment (McKibbin, & Fernando, 2021).…”
mentioning
confidence: 99%
“…As of April 10, 2020; 1,521,252 people were diagnosed with a COVID-19 infection, and 92,798 died from the virus (WHO, 2020). With a case fatality rate estimated around 2-3% (Cao et al, 2020), COVID-19 represents a potent and salient global threat. So far, the health and economic impacts of COVID-19 have been subjected to extensive assessment (McKibbin, & Fernando, 2021).…”
mentioning
confidence: 99%
“…Both genders were 30-60 years old. Males had a greater case fatality rate (1.3% vs. 1.1%) (Yang Cao et al, 2020) [25] explain that the CFR vary between populations and over time, depending on the interplay between the causative agent of the disease, the host and the environment, as well as available treatments and quality of patient care (Yang Cao et al, 2020) [25] and added that the Distribution of COVID-19 CFR of the 209 countries/ territories included in the study The mean and median CFR worldwide are 3.31% and 2.19%, respectively with the highest rates found in Yemen (27%), West and North Europe (14%-19%), and North America (9%-12%, figure 2). Study of Yousef et al, 2022 [15] included several countries revealed that South America had the highest hospital period of stay is 21 day whereas Africa had the lowest at 9 day the >60 age group had the highest hospitalization period of 16.day while the 40 age group had the lowest hospitalization period of 10day so this duration varies depending on a number of factors, including the patient's age and the availability of resources.…”
Section: Covid-19 and Healthcare Workersmentioning
confidence: 99%